2015
DOI: 10.1002/psp.1997
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Skill Shortages? Migration and the Australian Labour Market

Abstract: Although recent circumstances have rekindled interest in matching skilled migrant intakes to domestic labour needs, the factors contributing to migrant employment outcomes remain poorly understood. Contemporary research tends to focus on the best and worst of skilled migrant outcomes – either integration into elite transnational labour markets or relegation to relatively menial work. By approaching the issue from a perspective attuned to differentiated labour markets and their multiple segmentations, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…Demand for accounting and finance skills in Australia has been boosted by the financialization of the economy and growth of the mining and resource extraction sectors in recent decades (Weller, 2017;Yap et al, 2014). As a response, the government included accounting in the Migration Occupations in Demand List (MODL) in 2004 (Yap et al, 2014: 563).…”
Section: Research Context: Migrant Professionals In Australiamentioning
confidence: 99%
See 3 more Smart Citations
“…Demand for accounting and finance skills in Australia has been boosted by the financialization of the economy and growth of the mining and resource extraction sectors in recent decades (Weller, 2017;Yap et al, 2014). As a response, the government included accounting in the Migration Occupations in Demand List (MODL) in 2004 (Yap et al, 2014: 563).…”
Section: Research Context: Migrant Professionals In Australiamentioning
confidence: 99%
“…Between 2005 and 2012, accounting has been the occupation under which the highest number of skill-based residencies was granted; an average of more than 9000 migrants were admitted to Australia based on skills assessment in accounting between 2005 and 2012 (Department of Immigration andCitizenship, 2005-2012). Until 2011, migrant intake in the occupations listed under the MODL was uncapped (Weller, 2017). Studies have shown that migrants who received permanent residency based on skills assessed for accounting work in a range of occupations variously related to accounting, including clerical, administrative, and bookkeeping jobs (Weller, 2017).…”
Section: Research Context: Migrant Professionals In Australiamentioning
confidence: 99%
See 2 more Smart Citations
“…While the growth in international students completing studies in Australia was anticipated to address the skills shortage in the accounting profession, a lack of English language proficiency has meant that skills shortages continue (Weller ). This is demonstrated by the poor full‐time employment outcomes for international accounting graduates (DEEWR ).…”
Section: Literature Reviewmentioning
confidence: 99%